2019
DOI: 10.11157/anzswj-vol31iss2id632
|View full text |Cite
|
Sign up to set email alerts
|

Banging the same old colonial drum? Moving from individualising practices and cultural appropriation to the ethical application of alternative practices in social work

Abstract: INTRODUCTION: Western conceptualisations of social work are increasingly interestedin practices considered to be alternative or non-traditional to respond to oppression. While incorporating alternative methods into social work is frequently viewed as unproblematic, we suggest critical reflection is necessary to safeguard against inadvertent, culturally unsafe practice and the uncritical re-inscription of individualised solutions.APPROACH: In this article, we explore the application of group drumming practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Given the identified gap between practitioner's intentions to meaningfully include children's voices in practice, critical reflection was employed as both a research and educational strategy as it has been shown to effectively transform practice and address issues that concern both organisations and practitioners (see for example, [46,[51][52][53][54][55][56]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the identified gap between practitioner's intentions to meaningfully include children's voices in practice, critical reflection was employed as both a research and educational strategy as it has been shown to effectively transform practice and address issues that concern both organisations and practitioners (see for example, [46,[51][52][53][54][55][56]).…”
Section: Methodsmentioning
confidence: 99%
“…As a research methodology, critical reflection fortifies the link between research, theory, knowledge, and practice [51,57] by enlisting the research participants as co-inquirers [58] to generate effective practice strategies [46,51,[53][54][55][56]. In this research, critical reflection is being used to address the difficulties identified in implementing child-inclusive intentions into practice.…”
Section: Methodsmentioning
confidence: 99%
“…This method enables the reconstruction of common truths in a new, critical manner. Curtis and Morley (2019) point to the significance of acknowledging the underlying, nuanced ways in which social workers themselves contribute to the construction of the social order. Such acknowledgement may enable emancipation, exposing the nuanced hegemonic levels of operation and making it possible for social workers to develop professional perspectives that are less influenced by the hegemonic rationality.…”
Section: Critical Reflectionmentioning
confidence: 99%